HEALTH PERFORMANCE AUDIT - Maisigova Leila A.; Niyazbekova Shakizada; Karpenko Oksana Alekeevna; Aimakova Gulsim Targynovna; Moldashbayeva Luiza Polathanovna; Amanova Gulnara (Scientific Journal of Pedagogy and Economics, 2021)
The article discusses the directions and key issues of audit of efficiency in healthcare in foreign countries and in Russia. The analysis of the impact of the performance audit on the solution of socially important problems of maintaining public health is carried out. The authors determined the purpose of the audit of efficiency in the health sector, which is to promote the financial interests of the state, to ensure public health needs, to support accountability and responsibility regarding the activities of healthcare institutions. The medical effectiveness of healthcare institutions is determined as the degree of achieved results in the diagnosis, treatment, prevention, rehabilitation of patients, which is expressed as a percentage (or shares) based on the ratio of the number of cases of achieved results to the total number of observations. The absence of a specialized and legislatively fixed list of executive bodies endowed with control and supervisory powers in relation to healthcare institutions was noted. It was revealed that the requirement to exercise control related to the licensing functions of state supervision in Russia has not been established. Based on a study of foreign practice of financial control, it was found that performance audits represent a significant proportion of the control measures taken, and is the most progressive form of financial control. The article systematizes the bodies for monitoring compliance with mandatory requirements for goods, works and services at the level of medical institutions. Their non-systematic work, lack of interconnection in the implementation of supervisory activities as a factor that reduces the effectiveness of their authority is revealed.